An expert review on breaking barriers in severe asthma in Brazil: Time to act. (21st June 2021) - Pitrez, Paulo Márcio; Giavina-Bianchi, Pedro; Rizzo, José Ângelo; Souza-Machado, Adelmir; Garcia, Guilherme Freire; Pizzichini, Marcia Margaret Menezes
Currently, Brazil lacks a national asthma management program and is burdened with nearly 200, 000 hospitalizations due to the disease per year and approximately 5 deaths per day. The purpose of this article was to analyze the current issues surrounding severe asthma in Brazil, as the status of diagnosis and treatment is largely unknown, and to provide feasible recommendations to elicit imminent action. A panel of Brazilian medical experts in the field of severe asthma was provided with a series of relevant questions to address prior to a multi-day conference. Within this conference, each narrative was discussed and edited by the entire group. Through numerous rounds of discussion consensus was achieved. In order to overcome barriers to adequate asthma treatment, this panel recommends specific initiatives that can be implemented in the short-term to decrease the burden of severe asthma in Brazil. With increasing healthcare costs and limited resources globally, there is an opportunity to implement these recommendations in other countries in order to achieve adequate asthma care. Severe asthma is a heterogeneous and complex disease with various phenotypes that requires strict attention for diagnosis and management. Although this disease affects only a small proportion of the population with asthma, it poses a great burden to healthcare systems. Thus, barriers to diagnosis, treatment, and management should be overcome as quickly and efficiently as possible.